2016
DOI: 10.1515/aoas-2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Broiler Breeders’ Age on Eggshell Temperature, Embryo Viability and Hatchability Parameters

Abstract: High production of broiler meat depends on various factors, such as genetics, environmental conditions, nutrition, incubation process, etc. As a result, adequate keeping of broiler breeders and frequent analysis of hatchability results seem to be key factors for efficient production of high quality chicks.A significant impact of females' age on morphology and quality of eggs on reproductive performance were proved and described in many scientific publications *Work finsnced from DanHatch Poland S.A. and statut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…However, Abudabos (2010) showed that the best hatchability was obtained from hens at 26 weeks (Cobb 500 line) and 32 weeks (Ross 308 line) of age. Our results were similar to those of Nowaczewski et al (2016), who demonstrated the best hatchability in eggs laid by hens aged 40 weeks. However, our research indicated that the Ross 308 line at age 52 weeks had the best hatchability.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, Abudabos (2010) showed that the best hatchability was obtained from hens at 26 weeks (Cobb 500 line) and 32 weeks (Ross 308 line) of age. Our results were similar to those of Nowaczewski et al (2016), who demonstrated the best hatchability in eggs laid by hens aged 40 weeks. However, our research indicated that the Ross 308 line at age 52 weeks had the best hatchability.…”
Section: Discussionsupporting
confidence: 91%
“…This may be indicative of a properly balanced feeding regime among the tested hens. On the other hand, many authors showed that the reduced hatchability of the eggs from the older broiler breeders may be caused by many factors, including a larger egg size (Nowaczewski et al 2016), poorer shell quality (Iqbal et al 2016) or a deterioration in the albumen quality (Tona et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the limited air passage due to the coating of egg with chitosan. Nowaczewski et al (2016) reported that the eggshell temperature was 37.9°C in eggs on the 18 th day of incubation obtained from hens of 46-64 weeks of age.…”
Section: Re Sults and Discussionmentioning
confidence: 99%